169 reduction of hospital acquired MRSA bacteremias further to implementation of a continuous quality improvement program centered on cross-transmission prevention and antibiotic stewardship. (23rd September 2015) - Chalfine, Annie; Misset, Benoît; Kitzis, Marie-Dominique; Bezie, Yvonnick; Perniceni, Laurence; Nguyen, Jean Claude; Vidal, Barbara; Loriau, Jérôme; Couzigou, Carine; Dumay, Marie-Françoise; Carlet, Jean
Abstract : Context and objectives: The rates of methicillin resistant staphylococcus aureus (MRSA) in France has been over 25% from 2000 to 2007, higher than in most European countries in the earss surveillance program. Hospital acquired bacteremias due to MRSA are one of the best markers of the clinical impact of cross-transmission. The strategies designed to prevent hospital diffusion of MRSA are centered on isolation precautions and antibiotic stewardship. We implemented a program at the hospital level, combining these two approaches, and we measured its impact on the incidence of the patients acquiring colonisation or bacteraemia during their hospital stay since 2000. In our hospital before 2000, the infectious disease team and the infection control unit had failed to reduce hospital acquired MRSA carriage and bacteraemia despite continuous actions of antibiotic prescription counselling, MRSA detection and isolation of carriers. Our hospital had 450 acute beds in 2000 progressively rising to 600 in 2008 due to government driven hospital restructuring plans in the parisian area. All the medical and surgical specialities are available except neurosurgery. From 2000 to 2003, the following measures were successively implemented: hand disinfection with alcohol based hand rubs, control and counselling for the use of certain antibiotic classes, assessment of the care providers compliance to isolation measures, as well as feed back to care providers of the information regarding the principal indicators collected at the hospital level, and in the ICU and several high risk units, active screening and decontamination of the MRSA carriers. The impact of this program was assessed by measuring the incidence of both hospital acquired MRSA carriage and bacteremias for 1000 patient-days, in those patients hospitalised for more than 24 h. Results: The compliance of the personnel to isolation measures increased over years, as soon as audits were implemented. The use of alcohol based hand rubs was implemented in the entire hospital over 2 years and their consumption then increased progressively from 7 l per 1000 patient-days. The use of quinolones and third generation cephalosporins decreased by around 25%. the annual incidence of hospital acquired MRSA colonisation and bacteremias per 1000 patient-days decreased by 61% and 88% respectively. The ratio between 'hospital acquired' and 'imported from the community' MRSA carriers decreased from 1.1 in 2000 to 0.15 in 2009. Discussion: As we used a 'before-after' design, the decrease of hospital acquired infections we observed may have been due to other innovations than the program itself, and particularly to the reduction in the imported cases. Also, the active screening of the carriers was not performed in all the units, which may have led to an overestimation of the number of the hospital acquired cases. However, the same strategy was used throughout the program and the same results were observed within the ICU were active screening and decontamination was performed, favouring an important role of our program in these good results. Eventually, we did not perform a cost-benefit analysis of our program. Conclusion: Over a 10-year period, a continuous quality improvement program, combining strategies against both cross-transmission and antibiotic selection pressure was associated to a marked reduction in acquired MRSA bacteremias in our hospital. Contexte et objectifs: La proportion des staphylocoques dorés résistants à la méthicilline (sarm), d'après le programme de surveillance earss, était au dessus de 25% en france de 2000 à 2007, plus élevée que dans la plupart des autres pays européens. Les bactériémies à sarm survenant à l'hôpital représentent l'un des meilleurs marqueurs de l'impact clinique de la transmission croisée. Les stratégies destinées à éviter la diffusion hospitalière des sarm sont basées les précautions d'isolement et sur le contrôle des prescriptions antibiotiques. Nous avons implanté un programme à l'échelon de l'ensemble de l'hôpital, combinant ces deux approches, et mesuré son effet sur l'incidence des patients présentant une colonisation ou une bactériémie à sarm acquise au cours de leur séjour hospitalier depuis 2000. Dans notre hôpital avant 2000, l'équipe mobile de maladies infectieuses et l'équipe d'hygiène hospitalière n'avait pas réussi à réduire le portage et les bactériémies des sarm acquises à l'hôpital malgré des actions continues de conseil antibiotique, de détection et d'isolement des porteurs de sarm. Notre hôpital comportait 450 lits mco en 2000, augmentant progressivement à 600 lits mco en 2008 du fait de restructurations hospitalières. toutes les disciplines médicales et chirurgicales y sont exercées à l'exception de la neurochirurgie. de 2000 à 2003, les mesures suivantes ont été implantées successivement: la désinfection des mains avec une solution hydro-alcoolique, le contrôle et le conseil pour l'utilisation de certaines classes d'antibiotiques, l'évaluation de la compliance des personnels aux mesures d'isolation, ainsi que le retour d'informations à l'encadrement et aux personnels de santé concernant les principaux indicateurs relevés à l'échelon de l'hôpital entier et, dans le service de réanimation et quelques services à risque particulier, la détection systématique et la décontamination des patients porteurs de sarm. l'efficacité de ce programme a été évalué en mesurant l'incidence du portage et des bactériémies à samr acquises à l'hôpital pour 1000 journées/patient, chez les patients hospitalisés plus de 24h. Résultats: La compliance des personnels aux mesures d'isolement a augmenté au cours des années dès lors que les audits ont été mis en place. les solutions hydro-alcooliques ont été implantées sur l'ensemble de l'hôpital en deux ans et leur consommation a ensuite augmenté progressivement de 7 à 24 litres pour 1000 journées/patient. l'utilisation des quinolones et des céphalosporines de 3ème génération a diminué de 25% environ. l'incidence annuelle des porteurs et des bactériémies à sarm acquises à l'hôpital pour 1000 journées/patient a diminué respectivement de 61% et de 88%. le rapport entre les sarm acquis et les sarm importés a diminué de 1, 1 en 2000 à 0, 15 en 2009. Discussion: La comparaison étant de type « avant - après », nos résultats en terme de décroissance des infections acquises à sarm peuvent avoir été liées à d'autres éléments que le programme de prévention lui-même, et en particulier à la réduction de l'incidence des cas importés. par ailleurs, la détection systématique des patients colonisés à sarm n'a pas été effectuée dans tous les services, ce qui peut avoir surestimé le nombre de cas « acquis à l'hôpital ». cependant, d'une part la même stratégie de détection a été utilisée tout au long de la période, et, d'autre part, le même type de résultats a été observé dans le service de réanimation au sein duquel la détection systématique était effectuée, ce qui plaide pour un rôle important de notre programme dans ces bons résultats. enfin, nous n'avons pas effectué d'analyse coût-bénéfice de notre programme. Conclusion: Sur une période de 10 ans, un programme d'amélioration continue de la qualité qui combine des stratégies destinées à réduire la transmission croisée et la pression de sélection antibiotique a été associé à une réduction marquée des bactériémies à samr acquises dans notre hôpital.